Emergence of X states in a quantum impurity model - Moallison F. Cavalcante; Marcus V. S. Bonança; Eduardo Miranda; Sebastian Deffner (Physical Review Research)
In the present work, we demonstrate the emergence of X states in the long-time response of a locally perturbed many-body quantum impurity model. The emergence of the double-qubit state is heralded by the lack of decay of the response function as well as the out-of-time order correlator, signifying the trapping of excitations and hence information in edge modes. Surprisingly, after carrying out a quantum information theory characterization, we show that such states exhibit genuine quantum correlations.